FAKTOR PENENTU MINAT INVESTASI REKSA DANA SYARIAH - Astriana, Nahya; Jaharuddin, Jaharuddin (Taksasila Edukasi Insani, 2025)
This study examines the effects of Islamic financial literacy, income, and risk perception on investment interest in Islamic mutual funds, as well as the role of Islamic religiosity as a moderating variable. A quantitative explanatory approach was employed, with data collected through an online questionnaire from 316 Muslim respondents in Indonesia. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that Islamic financial literacy, income, and Islamic religiosity have a positive and significant effect on investment interest in Islamic mutual funds, with income identified as the most dominant factor. In contrast, risk perception does not significantly influence investment interest. The findings also indicate that Islamic religiosity does not act as a moderating variable but has a direct effect on investment interest. The proposed model explains 46.8% of the variance in investment interest. These findings suggest that investment decisions in Islamic mutual funds are driven more by financial capability and religious values than by risk considerations, highlighting the importance of strengthening Islamic financial literacy and expanding access to Islamic mutual fund products.Keywords: Islamic financial literacy, income, risk perception, Islamic religiosity, investment interest.